Rare bird documentation form for Northern Goshawk at Hickory Hill Park, 1981 - Hollis, Richard Juleet al (1981)
Rare bird documentation form for a Northern Goshawk at Hickory Hill Park in Johnson County, IA on November 15, 1981. Epson - sheet feed